Molecular dissection of Alternaria brassicicola pathogenesis mechanisms - Cramer, Robert Andrew, Jr., author; Lawrence, Christopher B., advisor; Knudson, Dennis L., committee member; Ishimaru, Carol A., committee member; Stargell, Laurie A., committee member (Colorado State University. Libraries, 2004)
Alternaria brassicicola is a necrotrophic fungal pathogen that causes black spot disease on cruciferous plants including economically important Brassica species and the model plant Arabidopsis thaliana. The purpose of this dissertation was to gain a better understanding of the pathogenesis mechanisms employed by A. brassicicola by identifying and cloning candidate pathogenicity genes. A functional genomics based approach was used to identify candidate pathogenicity genes by creating two suppression subtractive hybridization (SSH) libraries enriched for A. brassicicola genes during fungal pathogenesis, and one full length cDNA library of genes expressed during nitrogen starvation. The first library was created to be enriched for genes expressed during spore germination on the plant leaf surface using SSH. To create this library, RNA was isolated from A. brassicicola spores incubated in water and on the leaf surface of the Arabidopsis ecotype Landsberg. Two populations of cDNA were created from total RNA extracted after 24 hours when approximately 80% of the spores had germinated either on the leaf surface or in water and used in SSH. Differentially expressed genes were further screened with RT-PCR and cDNA northern blots. Five sequences were found to be of particular interest as they were expressed on the plant leaf surface but not during spore germination in water according to cDNA northern blots. These five cDNAs were predicted to encode a cyanide hydratase, arsenic ATPase, formate dehydrogenase, major Alternaria allergen, and one unknown. A second SSH library was generated from A. brassicicola infected green cabbage plants at 2, 4, and 6 days post-inoculation. Total RNA was pooled from these infection time points and uninfected cabbage and used to create cDNA for use in SSH. This created a library enriched for genes expressed during A. brassicicola pathogenesis. A total of 4224 expressed sequence tags (ESTs) were sequenced and assembled into a 3112 unisequence set using the assembly program CAP3. This unisequence set contained 608 contigs and 2504 singletons. The library had an estimated redundancy rate of 26%. BLAST algorithms were used to search publicly available databases to gain putative identities of the ESTs. BLAST searches identified 315 of the sequences as A. brassicicola, 1554 as cabbage, and 1243 as unknown. The unisequence set was run through the INTERPRO database and combined with the BLAST results to give Gene Ontology (GO) annotations of the ESTs. A similar analysis was conducted on a cDNA library created from A. brassicicola nitrogen starved mycelia. This full length cDNA library contained 1660 unisequences (253 contigs and 1407 singletons). Many ESTs from the infected cabbage and nitrogen starvation libraries had homology with known fungal pathogenicity factors. These included genes such as: ABC transporters, MAP kinases, polyketide synthases, serine proteases, and various plant cell wall degrading enzymes. One of the genes identified in all of the libraries had significant homology with the major Alternaria allergen Alt a 1. Phylogenetic analysis of Alt a 1 homologs from other Alternaria species revealed that this gene is highly conserved across the genus indicating a possible important function in Alternaria biology. Homologous recombination was used to disrupt the cyanide hydratase gene identified in the spore germination library to assess its role in fungal pathogenesis. Cyanide hydratase mutants were found to have increased sensitivity to varying concentrations of cyanide in vitro. However, cyanide hydratase mutants still caused wild-type black spot lesions on various Brassica species. This indicates that cyanide hydratase is likely not required for fungal pathogenesis. One fungal gene of particular interest contained in the library was a homolog of the fungal pathogenicity MAP kinase, PMK1. Random amplification of cDNA ends (RACE) was used to obtain a full length copy of the Alternaria PMK1 homolog, AMK1. Degenerate PGR was used to clone another MAP kinase known to be involved in cell wall integrity and was named AMK2. Phylogenetic analysis of these 2 MAP kinases revealed that they are likely homologs of known fungal pathogenicity factors. The results of this dissertation provide the first insight into genes expressed during A. brassicicola infection of Brassica species that may be involved in fungal pathogenesis. A total of 2,002 A. brassicicola candidate genes were identified. Future studies will involve further characterization of important fungal genes identified in the libraries generated during the course of this research.
Keywords: molecular biology